Analisis Dampak Sosial Zakat, Infak, dan Sedekah terhadap Kesejahteraan Masyarakat Berpenghasilan Rendah - Rofiqo Meili Mahera; Murah Syarial (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The writing of this article describes the Role of Zakat, Alms and Infaq in Minimizing Economic Disparities in Society according to Islamic teachings. The research method used is internet searching. From the data obtained, it is then analyzed and reviewed in depth based on the references used. This article explains that basically it can be assumed that zakat is a gift with conditions and measurements and is mandatory, infaq and shadaqah are gifts without conditions and measurements. In the Islamic view, giving their wealth to others in need can purify their souls and also as a reminder that the wealth is not theirs, but belongs to Allah SWT which is entrusted to them. Therefore, this article aims to provide an understanding to Muslims so that they know the meaning and benefits of zakat, alms and infaq. And believe that the more you give, the more Allah SWT will give you many times over in the afterlife.